The contribution of mLearning to study of local culture in the Malaysian university context (IR) - Shamsul Arrieya Ariffin (2014)
This thesis is concerned with the impact of mobile learning (mLearning) on the study of local culture at Malaysian universities. For convenience, the term Local Cultural Studies (LCS) is given to Humanities subjects related to the teaching and learning of Malay culture, for example: Local History, Local Culture and National Heritage, Malay Wood Craft, Malay Drum, Cooking, Batik Textile, Ceramic, and Local Drama. These subjects are not as popular as Science and Engineering and are often referred to as 'dying traditional knowledge' with an uncertain future. They have a lesser degree of significance in modem Malaysian society in achieving a 'developed country' status. One motivation for introducing mLearning into LCS subjects is to make them more interesting: the learning activities and the subjects should appear more modem by linking them to the latest technology. The fact that all students own mobile phones in Malaysian universities creates an opportunity to use mLearning for the benefit of LCS. In addition, mLeaming could be used to create student-generated content to richer multimedia learning resources as one of the major challenges for LCS is the limited ability of resources. An exploratory preliminary study with managers and content lopers within mobile application companies confirmed there were limited local mobile ent and little incentive to develop more. A major focus of this thesis was to investigate approaches to overcoming this problem: (1) the development of culturally appropriate face design guidelines that could be used to assist developers and academics in the uction of local content; and (2) involving students in creating local content in studentrated mLearning activities. largely qualitative study focused on gammg an understanding of mLearning's ributions to the study of local culture from the perspective of academics and students at ominantly Malaysian public universities. The research was designed in two stages. In e 1, Nielsen's user interface design guidelines were first adapted to include two cultural